Defects and improving the maintainability of buildings at the advance technical training centres [electronic resource] - Rajandran Suppiah Raman, 1958- (2011)
Thesis (Sarjana Sains (Pengurusan Aset dan Fasiliti)) - Universiti Teknologi Malaysia, 2011